How do you simplify (4-2i)(6+6i)?

1 Answer
Aug 26, 2016

You have to cross-multiply the two factors (4−2i)(6+6i) as if they were factors of a quadratic.

Explanation:

Remember FOIL? First terms, Inside terms, Outside terms, Last terms. Do this first.

Next, combine like terms.

Lastly, recognize that i^2 equals - 1, and take that into account.

So, let's multiply (4−2i)(6+6i) :
4 * 6 = 24
4 * 6i = 24i
- 2i * 6 = - 12i
- 2i * 6i = - 12i^2

Since i^2 = - 1, we have - 12i^2 = + 12.

Add all the answers we got above:

24 + 24i - 12i +12

Combine the two i terms:

24i - 12i = + 12i, and so far we have:

24 + 12i + 12

Combine the constants ( 24 + 12) and we get:

36 + 12i.